FUNGSI HUKUM DALAM MEWUJUDKAN KEMITRAAN ANTARA PENGELOLA PENDIDIKAN DAN MASYARAKAT UNTUK MENINGKATKAN MUTU PELAYANAN PENDIDIKAN - Seto Cahyono (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Management of education is not just governmental responsibility but also is society responsibility. Because Indonesia is Body Politic, hence is of course law have to function better, one ofthe the function of law can be used as medium to push changes of development and social. With existence that sure and clear law and regulation or law partner between to manage society and education to upgrade service of education. Mean society generally do not hesitate law it is true function better, although there is constraint-constraint faced.